Suyima G‘aniyeva’s Scientific Views on Alisher Navoi’s Heritage - Baxtiyorova Madina (Zamonaviy ta’lim va tilshunoslik rivoji, 2026)
This article discusses the scientific activity of Suyima G‘aniyeva in studying the heritage of Alisher Navoiy. The scholar’s contribution to the study of the textual, artistic, and spiritual features of Navoi’s works is analyzed. The article also highlights her role in the development of Navoi studies.